2016
DOI: 10.1038/cddis.2016.138
|View full text |Cite
|
Sign up to set email alerts
|

Erianin induces G2/M-phase arrest, apoptosis, and autophagy via the ROS/JNK signaling pathway in human osteosarcoma cells in vitro and in vivo

Abstract: Erianin, a natural product derived from Dendrobium chrysotoxum, has exhibited potential antitumor activity in various malignancies, including hepatocarcinoma, melanoma, and promyelocytic leukemia. Here we explored the effects of erianin on osteosarcoma (OS) in vitro and in vivo and further elucidated the underlying molecule mechanisms. In this study, we found that erianin potently suppressed cell viability in various OS cell lines. Treatment with erianin induced G2/M-phase arrest, apoptosis, and autophagy in O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
144
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(166 citation statements)
references
References 45 publications
17
144
2
3
Order By: Relevance
“…Natural bioactive compounds derived from traditional Chinese medicinal herbs have been widely investigated because of their antiproliferative, antiangiogenic, and antitumor effects on various diseases, as well as their safety, efficacy and immediate availability. The effects of natural compounds on the inhibition of osteosarcoma have previously been reported by our research team . For instance, we found that pectolinarigenin significantly suppressed osteosarcoma cell proliferation, induced apoptosis and inhibited migration and invasion in osteosarcoma cells .…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Natural bioactive compounds derived from traditional Chinese medicinal herbs have been widely investigated because of their antiproliferative, antiangiogenic, and antitumor effects on various diseases, as well as their safety, efficacy and immediate availability. The effects of natural compounds on the inhibition of osteosarcoma have previously been reported by our research team . For instance, we found that pectolinarigenin significantly suppressed osteosarcoma cell proliferation, induced apoptosis and inhibited migration and invasion in osteosarcoma cells .…”
Section: Discussionsupporting
confidence: 72%
“…Alternol, a novel compound purified from microbial fermentation products, not only inhibited osteosarcoma cell proliferation and migration and induced caspase‐dependent apoptosis and G2/M cell cycle arrest in vitro, but also suppressed tumor growth in an orthotopic tibial osteosarcoma model . In addition, our team has demonstrated that two natural compounds, toosendanin and erianin, suppress human osteosarcoma growth and metastasis . The results of the present research indicate that RA, a natural bioactive compound, significantly suppressed cell proliferation and induced apoptosis in a dose‐ and time‐dependent method.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This crosstalk could be mediated by the interactions between Beclin-1 and Bcl-2/Bcl-xL and between FADD and Atg5, caspase- and calpain-mediated cleavage of autophagy-related proteins, and autophagic degradation of caspases [9–13]. Reactive oxygen species (ROS) plays important roles in mediating apoptosis and autophagy in response to a panel of natural products such as evodiamine [14], oridonin [15], graveoline [16], total tanshinones [17], and erianin [18]. …”
Section: Introductionmentioning
confidence: 99%
“…144 Schmid et al 145 reported the substantially greater potency of bpV (phen), bpV (pic), and bpV (HOpic) against PTEN than against the classical protein tyrosine phosphatases (PTPs), protein tyrosine phosphatase 1B (PTP1B), and protein tyrosine phosphatase B (PTPb). Moreover, they detected a bpV-mediated enhancement of insulin-stimulated AKT activation that was observed in cells expressing 154,155 SF1126 (LY294002) LY294002 is the first synthetic molecule known to inhibit PI3Kα/ÎŽ/ÎČ with IC50 of 0.5/0.57/0.97 ”M in cell-free assays, respectively, more stable in solution than Wortmannin, and also blocks autophagosome formation Mbengue et al, 156 Bolen et al, 157 Sapey et al 158 XL147 XL147 analogue is a selective and reversible class I PI3K inhibitor for PI3Kα/ÎŽ/Îł with IC50 of 39/36/23 nM in cell-free assays, less potent to PI3KÎČ. Phase 1/2…”
Section: Conclusion and Future Directions And Perspectivesmentioning
confidence: 99%